A study on the structure of anthracite based on benzene carboxylic acids. (October 2021) - Hou, Yucui; Yang, Fan; Yang, Chunmei; Feng, Ziliang; Feng, Lixia; Li, He; Ren, Shuhang; Wu, Weize
Abstract: Anthracite, a high-rank coal, is an important fossil energy and resource, widely used in combustion and gasification. To improve the utilization efficiency of anthracite, it is important to study its structures. In our previous work, we found that the alkali-oxygen oxidation of anthracite could yield benzene carboxylic acids (BCAs). However, none of the existing structural models of anthracite captures the yield distribution of BCAs. In this work, we studied the structures of Hebi anthracite based on its BCAs combined with multi analysis techniques and proposed a structural model of the coal. We first oxidized the coal to yield BCAs, whose parent structure distributions we then investigated. Then, based the results of ultimate analysis and 13 C NMR, we obtained the structural parameters. We then proposed corresponding aromatic clusters based on the parent structures of BCAs. Lastly, we constructed a structural model of the coal based on the analyses of ultimate analysis, 13 C NMR, XPS and the contents of carboxyl and phenolic hydroxyl groups. The model has a molecular formula of C1966 H882 N22 O76 S3 and a molecular weight of 26094 amu. The model not only reflects the characteristics of anthracite intuitively, but also agrees with the results of BCAs, elemental analysis, carboxyl and phenolic hydroxyl group analyses, XPS analysis, and 13 C NMR analysis. The work provides new insights in the structural characteristics of anthracite. Highlights: Benzene carboxylic acids were obtained from Hebi anthracite via oxidation. A structural model of Hebi anthracite was proposed based on the distributions of their yields. The model has a molecular formula of C1966 H882 N22 O76 S3 and a molecular weight of 26094 amu. The model can reflect the characteristics of anthracite.